Supplementary benefits of CT-guided transthoracic lung aspiration biopsy for core needle biopsy - He, Jia-Huan; Ruan, Jia-Xing; Lei, Ying; Hua, Zhi-Dan; Chen, Xiang; Huang, Da; Chen, Cheng-Shui; Jin, Xu-Ru (Frontiers in Microbiology, 2022)
Objective: This study aimed to investigate the diagnostic efficacy of computed tomography (CT)-guided transthoracic lung core needle biopsy combined with aspiration biopsy and the clinical value of this combined routine microbial detection. Conclusion: CT-guided lung aspiration biopsy has a significant supplementary effect on core needle biopsies, which is indispensable in clinical application. Additionally, the combination of aspiration biopsy and core needle biopsy can significantly improve the diagnostic rate of benign and malignant lesions. Aspiration biopsy showed that pulmonary malignant lesions are complicated with pulmonary tuberculosis, aspergillus, and other infections. Finally, the diagnostic ability of lung puncture core needle biopsy and aspiration biopsy combined with routine microbial detection under CT positioning in the diagnosis of pulmonary infectious diseases was significantly improved.